Museomics and the holotype of a critically endangered cricetid rodent provide key evidence of an undescribed genus - Castañeda-Rico, Susette; Edwards, Cody W.; Hawkins, Melissa T. R.; Maldonado, Jesús E. (Frontiers in Ecology and Evolution, 2022)
Historical DNA obtained from voucher specimens housed in natural history museums worldwide have allowed the study of elusive, rare or even extinct species that in many cases are solely represented by museum holdings. This has resulted in the increase of taxonomic representation of many taxa, has led to the discovery of new species, and has yielded stunning novel insights into the evolutionary history of cryptic or even undescribed species. Peromyscus mekisturus, is a critically endangered cricetid rodent endemic to Mexico and is only known from two museum specimens collected in 1898 and 1947. Intensive field work efforts to attempt to determine if viable populations still exist have failed, suggesting that this species is extinct or is nearing extinction. In addition, a recent study using mitogenomes demonstrated that P. mekisturus forms a well-supported clade outside the genus Peromyscus and hypothesized that this taxon is the sister group of the genus Reithrodontomys. Here, we used target enrichment and high-throughput sequencing of several thousand nuclear ultraconserved elements and mitogenomes to reconstruct dated phylogenies to test the previous phylogenetic hypothesis. We analyzed the holotype and the only other known specimen of P. mekisturus and museum samples from other peromyscine rodents to test the phylogenetic position of the species. Our results confirm that the only two specimens known to science of P. mekisturus belong to the same species and support the hypothesis that this species belongs to an undescribed genus of cricetid rodents that is sister to the genus Reithrodontomys. We dated the origin of P. mekisturus together with other speciation events in peromyscines during the late Pliocene – early Pleistocene and related these events with the Pleistocene climatic cycles. In light of our results, we recommend a taxonomic re-evaluation of this enigmatic species to properly recognize its taxonomic status as a new genus. We also acknowledge the relevance of generating genomic data from type specimens and highlight the need and importance of continuing to build the scientific heritage of the collections to study and better understand past, present, and future biodiversity.